The hidden RNA code: implications of the RNA epitranscriptome in the context of viral infections - Ribeiro, Diana Roberta; Nunes, Alexandre; Ribeiro, Daniela; Soares, Ana Raquel (Frontiers in Genetics, 2023)
Emerging evidence highlights the multifaceted roles of the RNA epitranscriptome during viral infections. By modulating the modification landscape of viral and host RNAs, viruses enhance their propagation and elude host surveillance mechanisms. Here, we discuss how specific RNA modifications, in either host or viral RNA molecules, impact the virus-life cycle and host antiviral responses, highlighting the potential of targeting the RNA epitranscriptome for novel antiviral therapies.